Distinguishing Cartesian Products of Countable Graphs - Estaji Ehsan (Discussiones Mathematicae Graph Theory, 2017)
The distinguishing number D(G) of a graph G is the minimum number of colors needed to color the vertices of G such that the coloring is preserved only by the trivial automorphism. In this paper we improve results about the distinguishing number of Cartesian products of finite and infinite graphs by removing restrictions to prime or relatively prime factors.